Pengaruh Kinerja Keuangan Dan Manajemen Risiko Terhadap Nilai Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Periode 2019-2024 - Mandam, Sri Yulandasari Lajai; Pujiyanti, Pujiyanti; Arrachman, Hajar Chair; Ferdian, Adam Devan; Alfiana, Alfiana (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
The purpose of this research is to review how financial performance and risk management affect the value of banking companies listed in the Indonesian capital market (IDX) during the period 2019 to 2024. The benchmark for financial performance is Return on Assets (ROA), while risk management is seen from Non Performing Loan (NPL), and the company’s value is measured using Price to Book Value (PBV). This research uses secondary data obtained from the annual financial statements of various banks published by BEI. The sampling technique used is purposive sampling, which produces several selected banks that meet the research criteria. The analysis was carried out with panel data regression, selecting a model through the Chow test, Hausman test, and the Lagrange Multiplier test, with the Fixed Effect Model (FEM) as the selected model. The research results revealed that separately, ROA has a positive impact although not significantly on the company’s value, while NPL has a negative impact that is also insignificant on the company’s value. However, through the F test, it was found that ROA and NPL together have a significant effect on the company’s value. The high coefficient of determination indicates that the research model is quite strong in explaining the change in corporate value in the banking sector. The conclusion of this research is that although each variable, both financial performance and risk management, does not show a significant influence individually, both still play an important role in determining the value of banking companies in Indonesia.